2020
DOI: 10.1136/bmjopen-2020-038871
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the mistreatment of childbearing women: evaluation of respectful maternity care intervention in Ethiopian hospitals

Abstract: ObjectivesThere is a lack of evidence on approaches to mitigating mistreatment during facility-based childbirth. This study compares the experiences of mistreatment reported by childbearing women before and after implementation of a respectful maternity care intervention.DesignA pre–post study design was undertaken to quantify changes in women’s experiences of mistreatment during facility-based childbirth before and after the respectful maternity care intervention.InterventionA respectful maternity care interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Here, I am largely drawing from an implementation research from Ethiopia that explored health system constraints to the promotion of RMC in public hospitals and tested a multicomponent intervention (staff training, placement of wall posters and post-training onsite support for quality improvement) that was designed to promote RMC. [18][19][20] The study used an interventional mixed methods design that included surveys of both women and service providers before and after the intervention, focus group discussions with service providers before and after the intervention and in-depth interviews with key informants before the intervention. Based on the findings of the study and other implementation studies from Kenya, Nigeria and Tanzania, [21][22][23] I have synthesised approaches to the promotion of RMC (figure 1).…”
Section: Rmc From the Perspectives Of People-centred Healthcarementioning
confidence: 99%
“…Here, I am largely drawing from an implementation research from Ethiopia that explored health system constraints to the promotion of RMC in public hospitals and tested a multicomponent intervention (staff training, placement of wall posters and post-training onsite support for quality improvement) that was designed to promote RMC. [18][19][20] The study used an interventional mixed methods design that included surveys of both women and service providers before and after the intervention, focus group discussions with service providers before and after the intervention and in-depth interviews with key informants before the intervention. Based on the findings of the study and other implementation studies from Kenya, Nigeria and Tanzania, [21][22][23] I have synthesised approaches to the promotion of RMC (figure 1).…”
Section: Rmc From the Perspectives Of People-centred Healthcarementioning
confidence: 99%
“… 36 The survey of women revealed that the number of mistreatment components women experienced during childbirth in the study hospitals was reduced by 18% after the RMC intervention. 37 The mixed-methods study revealed that service providers’ awareness of the rights of childbearing women, perceptions and attitudes about RMC, and motivation to provide respectful care improved after the RMC intervention. 36 …”
Section: Discussionmentioning
confidence: 98%
“…In two other studies, we have reported on the evaluation of the RMC intervention (survey of women before and after the intervention) 37 and the lessons learned through its implementation, including the enablers of RMC (mixed-methods study among service providers who participated in the intervention). 36 The survey of women revealed that the number of mistreatment components women experienced during childbirth in the study hospitals was reduced by 18% after the RMC intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, avoidance of ill-treatment and disrespectful care during childbirth is simple but determinant for better maternal health outcomes and the good adherence of women to maternal and neonatal health services given during the postnatal period. 16 However, a lot of women were treated disrespectfully at the time of childbirth and other obstetric care. 14 One in three women is subjected to abuse and violence during labor and delivery.…”
Section: Introductionmentioning
confidence: 99%